Spatial distribution of physiologic 12-lead QRS complex - Hnatkova, Katerina; Andršová, Irena; Toman, Ondřej; Smetana, Peter; Huster, Katharina M; Šišáková, Martina; Barthel, Petra; Novotný, Tomáš; Schmidt, Georg; Malik, Marek (Scientific reports, 2021)
The normal physiologic range of QRS complex duration spans between 80 and 125 ms with known differences between females and males which cannot be explained by the anatomical variations of heart sizes. To investigate the reasons for the sex differences as well as for the wide range of normal values, a technology is proposed based on the singular value decomposition and on the separation of different orthogonal components of the QRS complex. This allows classification of the proportions of different components representing the 3-dimensional representation of the electrocardiographic signal as well as classification of components that go beyond the 3-dimensional representation and that correspond to the degree of intricate convolutions of the depolarisation sequence. The technology was applied to 382,019 individual 10-s ECG samples recorded in 639 healthy subjects (311 females and 328 males) aged 33.8 ± 9.4 years. The analyses showed that QRS duration was mainly influenced by the proportions of the first two orthogonal components of the QRS complex. The first component demonstrated statistically significantly larger proportion of the total QRS power (expressed by the absolute area of the complex in all independent ECG leads) in females than in males (64.2 ± 11.6% vs 59.7 ± 11.9%, p < 0.00001-measured at resting heart rate of 60 beats per minute) while the second component demonstrated larger proportion of the QRS power in males compared to females (33.1 ± 11.9% vs 29.6 ± 11.4%, p < 0.001). The analysis also showed that the components attributable to localised depolarisation sequence abnormalities were significantly larger in males compared to females (2.85 ± 1.08% vs 2.42 ± 0.87%, p < 0.00001). In addition to the demonstration of the technology, the study concludes that the detailed convolution of the depolarisation waveform is individual, and that smoother and less intricate depolarisation propagation is the mechanism likely responsible for shorter QRS duration in females.
Keywords: Electrocardiography; Male; Middle Aged; výpočetní biologie; srdce; sexuální faktory; Adult; dospělí; mužské pohlaví; Healthy Volunteers; algoritmy; analýza dat; lidé; ženské pohlaví; Humans; Sex Factors; elektrofyziologické jevy; Algorithms; zdraví dobrovolníci pro lékařské studie; Electrophysiological Phenomena; Female; Heart; Data Analysis; lidé středního věku; biologická variabilita populace; Computational Biology; Biological Variation, Population; elektrokardiografie